A importância dos 2 Vs – Velocidade e Variedade – do Big Data em situações de busca da internet: um estudo envolvendo alunos do ensino superior - Kadow, André Luis Dal Santo (2017)
The amount of digital data, structured or not, generated daily is enormous and it is possible to observe within society how the companies that hold this information end up using the mass information of the past to try to predict or even facilitate future behavior on the part of users. It is the concept of Big Data working on increasingly diverse fronts, driven by algorithms, Internet of Things (IoT) among others. However, having a large amount of data alone is not as representative as understanding and exploiting its use within the processes involved. Authors such as Turing, Searle and Andersen have already foreseen the importance and impacts of this myriad of data for a long time. The analysis of these different points of view is a starting point for the understanding of how autonomous systems that learn through data inputs captured or given spontaneously by the users were the essence to reach the central idea of this thesis, which is to analyze and understand the influence of two Big Data Vs - Speed and Variety - of Big Data within the digital life of young college students, using a class from a specific faculty for the case study